GAMBARAN TINGKAT STRESS GURU MADRASAH ALIYAH DI JAKARTA SELATAN SELAMA MASA PANDEMI - Siti Fathonah; Cahya Ramadani Renhoran (Jurnal Pendidikan Islam, 2021)
One year has passed since Covid-19 force us to stay at home and study through online classes. Changes of habits that require adaptation from the teacher, student's condition, boredom, and facility availability become obstacles that can increase stress levels among teachers. This research aimed to describe stress level among islamic senior high school teacher in South Jakarta during pandemic Covid-19. This research uses a quantitative method with a cross-sectional design. 147 samples collected using purposive sampling. Perceived Stress Scale questionnaire is used to collect the data. Data then processed with univariate and bivariate analysis using SPSS. 88 respondents classified as moderate stress level (59.9%), 54 respondents classified as mild stress level (36.7%), and 5 respondents classified as severe stress level (3.4%). Factors that correlate significantly with stress level are employee status (p-value = 0.044) and the type of school (p-value = 0.009).